Outcome and technical consideration of conversion total hip arthroplasty after failed fixation of intracapsular and extracapsular hip fractures: Are they really that different?. (March 2022) - De Meo, D.; Ferraro, D.; Petriello, L.; Zucchi, B.; Calistri, A.; Persiani, P.; Villani, C.
Highlights: Conversion THA on failure of extracapsular fracture fixation is more challenging. Type of hip fracture does not impact on functional outcome of conversion THA. Short stem could be used in conversion THA to treat specific failure pattern. Abstract: Introduction : Conversion Total Hip Arthroplasty (cTHA) is a rescue strategy for proximal femur osteosynthesis failures. However, it is unclear whether cTHAs performed for extra-capsular fracture fixation failures (ECF) or for intra-capsular fracture fixation failures (ICF) share the same complexity and efficacy. The purpose of our study was to compare cTHAs performed on pre-existing ICFs and pre-existing ECFs, focusing on surgical complications and functional outcomes in both groups. Methods: An observational retrospective study was conducted on cTHA patients, treated between 2014 and 2018, divided into 2 groups: ICF-group and ECF-group. The main outcomes were: type of implant used, duration of surgery, need for transfusions, incidence of complications, functional outcomes. Results : 28 patients were included (15 in the ECF group and 13 in the ICF group); the average follow-up was of 31 ± 17.3 months. No significant differences were identified in terms of the type of implant used and duration of surgery. The number of transfused patients was 4 in the ICF group and 12 in the ECF group ( p = 0.02); the average transfused units were 0.4 ± 0.7 in the ICF group and 1.3 ± 0.9 in the ECF group ( p = 0.01). The incidence of complications - an infection and a dislocation, both of which occurred in the ICF group - and functional outcomes did not present significant differences. Conclusion: The conversion surgery on ECFs patients is technically more difficult for the surgeon and prone to greater blood loss. The outcomes are satisfactory and overlap between the two groups.